“Vote for who you like; fight for the right party”: A case study of voting reasons in Thailand's Northeast in the 2023 general elections - Saowanee Alexander (Journal of Current Southeast Asian Affairs, 2025)
This paper explores voting reasons in Thailand's 2023 election in the Northeast. For a long time, this region has been considered a bastion of pro-democracy movements in the streets and parliament. While the recent election results still suggest so to a greater degree, the region has also witnessed big victories for parties positioning themselves to be staunch guardians of Thai conservatism. This is not to mention electoral surprises including dark horses whose victory has upset long-serving incumbent constituency members of parliament. Based on a textual analysis of questionnaire responses from voters of a wide range of demographic backgrounds, the paper explains the election outcomes in terms of voters’ political ideologies, needs, challenges, and strategies.